(3a - 2b)c = 15
Пошаговое объяснение:
А(-3:2:1) В(-1:1:3) С(-2:1:1).
сначала (3А - 2В)
3А - 2В = {3Аx - 2Вx; 3Аy - 2Вy; 3Аz - 2Вz} = {3*(-3) - 2*(-1); 3*2 - 2*1; 3*1 - 2*3} = {-9 - (-2); 6 - 2; 3 - 6} = {-7; 4; -3}
для простоты записи обозначим (3А - 2В) = Е = {-7; 4; -3}
теперь (3А - 2В)*С = Е*С
ЕС = Еx*Сx + Еy*Сy + Еz*Сz = (-7)*(-2) + 4*1 + (-3)*1 = 14 + 4 - 3 = 15
(3a - 2b)c = 15
Пошаговое объяснение:
А(-3:2:1) В(-1:1:3) С(-2:1:1).
сначала (3А - 2В)
3А - 2В = {3Аx - 2Вx; 3Аy - 2Вy; 3Аz - 2Вz} = {3*(-3) - 2*(-1); 3*2 - 2*1; 3*1 - 2*3} = {-9 - (-2); 6 - 2; 3 - 6} = {-7; 4; -3}
для простоты записи обозначим (3А - 2В) = Е = {-7; 4; -3}
теперь (3А - 2В)*С = Е*С
ЕС = Еx*Сx + Еy*Сy + Еz*Сz = (-7)*(-2) + 4*1 + (-3)*1 = 14 + 4 - 3 = 15